Synthesis, Characterization, and Spectroscopic Studies of Bis-(meso-4-methoxyphenyl)-Benziporphyrin and Its Pd-Metal Complex - Endale Mulugeta; Chang-Hee Lee (Journal of Chemistry)
Benziporphyrin systems are widely explored, yet alternative improved synthetic routes towards these systems are needed. Here, a fairly and efficient synthesis of the free base and its metal complex is well designed. Dimethoxybenzene dicarbinol intermediate was prepared in excellent yields by reacting 4-methoxyphenylmagnesium bromide with isophthaladehyde in diethyl ether. Reaction with equivalent pyrrole and pentafluorobenzaldehyde in the presence of trifluoroacetic acid (TFA), followed by oxidation with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), provided good yields of bis-(meso-4-methoxyphenyl)-benziporphyrin. Metalation of the free base was performed using palladium(II) acetate salt in acetonitrile. All intermediates and the final products are fully characterized using NMR, HMRS, and UV-Vis spectroscopies and briefly discussed.